Color-code Strategy for Improving Writing Academic Paragraphs in EFL Classes - Rebin Abdulkadir Azeez (Zanco Journal of Humanity Sciences)
In this semi quantitative study, the respondents were EFL students in Koya University, Faculty of education, and department of English Language. The aim was to inspect and scrutinize the effect of color-code strategy on their proficiency regarding writing academic paragraphs. They were 60 freshmen students who were studying in their first year levels. Both male and female participants were enrolled in two writing tests about writing descriptive paragraphs. The tests were conducted in the department, during studying writing skills subject in the second semester, and then their writings were analyzed using a rubric. Later, using Independent Samples t-test, the results were processed into numerical datum. The conclusion is that, color-coding strategy has impact on student's advancement in writing a well-structured paragraph in the post-test. Furthermore, students wrote their second paragraph with correct structure and organization. Therefore, the final results maintain that color-code strategy is a beneficial didactical mechanism to be used in the field of EFL and ESL teaching particularly in writing skills courses.